The Comparison of Institutional Model in Water Management Board - A Case Study of Management on Polder Drainage System in Semarang, Indonesia - Adi, Henny Pratiwi; Wahyudi, Slamet Imam (International Journal of Sustainable Construction Engineering and Technology, 2020)
Semarang is one of the cities in Indonesia which has a flood problem. Changes in land use, high rainfall intensity and erosion and sedimentation in river channels are the cause of flooding. Flood control has been attempted, such as the optimization of the drainage system. This study aims to obtain an appropriate institutional model for managing the drainage system. Research data obtained through literature and interviews with related parties in drainage management. There are three institutional models of drainage management systems that have been applied in Semarang, namely the government-based institutional model, the community-based institutional model, and the stakeholder-based institutional model. A total of 24 respondents from the elements of the city government, business people and the community were asked to assess the institutional model for drainage system management. The institutional model is analyzed in five aspects, namely technical, institutional, legal, financial, and community participation. Based on the results of the study, the most appropriate institutional model is the stakeholder-based institutional model. This institutional model has the advantage of involving many parties such as the government; communities and entrepreneurs, problems with the drainage system can be dealt with faster; have a legal umbrella that is protected by the government; and sources of funding for operational drainage systems can come from government and non-government.